2021
DOI: 10.3390/su14010052
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management and Experience Transfer in Major Maintenance Activities: A Practitioner’s Perspective

Abstract: Major overhauls, outages, shutdowns and turnarounds (MoOSTs) are significant maintenance interventions needed on a periodic basis to optimise the performance of physical industrial assets (PIAs). However, uncertainties in the forms of emergent and discovery work which sometimes cause delays and cost overruns are quite common partly because, MoOSTs are characterised by inherent challenges such as, but not limited to, short execution spans, volatility in ever-evolving schedules, task complexities as well as huge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Knowledge management is the process by which an organization manages its existing knowledge and creates new knowledge that can be used and distributed across all elements of the business in order to achieve the company's vision and goal while gaining a competitive advantage over competitors (Dávideková et al, 2020;Iheukwumere-Esotu & Yunusa-Kaltungo, 2022;Čizmić & Ahmić, 2021;Muskat & Mair, 2020). The dimensions of knowledge management used in this study are knowledge discovery, knowledge capture, knowledge sharing, and knowledge application.…”
Section: H1: There Is An Influence Of Talent Management On Job Satisf...mentioning
confidence: 99%
“…Knowledge management is the process by which an organization manages its existing knowledge and creates new knowledge that can be used and distributed across all elements of the business in order to achieve the company's vision and goal while gaining a competitive advantage over competitors (Dávideková et al, 2020;Iheukwumere-Esotu & Yunusa-Kaltungo, 2022;Čizmić & Ahmić, 2021;Muskat & Mair, 2020). The dimensions of knowledge management used in this study are knowledge discovery, knowledge capture, knowledge sharing, and knowledge application.…”
Section: H1: There Is An Influence Of Talent Management On Job Satisf...mentioning
confidence: 99%
“…However, scholars have been discussing knowledge sharing from a theoretical perspective. There are pages of well-written academic documents [14][15][16], but unfortunately, very few of which have approached knowledge sharing from a practical perspective and suggested a functional framework for knowledge sharing in SC. A knowledge sharing framework is one of the essential steps for building a comprehensive knowledge sharing policy in the SC [17].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Evidence has shown that virtually all HEIs are capable of developing graduate engineers that possess discipline‐specific expertise, but employers have continued to emphasize the criticality of employing graduate engineers that also complement their core technical expertise with more generic skills sets. The study by Hoddinott and Young 2 highlights that modern day employers, value graduate engineers with fundamental management characteristics in team‐working, creative thinking, problem solving and communication, in addition to their core technical engineering knowledge 3‐10 . The most popular approach for providing complementary knowledge within typical undergraduate engineering (UGE) curriculums is by embedding interdisciplinary units 11‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…The study by Hoddinott and Young 2 highlights that modern day employers, value graduate engineers with fundamental management characteristics in team-working, creative thinking, problem solving and communication, in addition to their core technical engineering knowledge. [3][4][5][6][7][8][9][10] The most popular approach for providing complementary knowledge within typical undergraduate engineering (UGE) curriculums is by embedding interdisciplinary units. [11][12][13][14][15] At the University of Manchester, for instance, students pursuing mechanical, aerospace, and civil engineering (MACE) degrees take project management, operations management, legal issues, enterprise management, and engineering foresight courses from Years 1-4.…”
Section: Introductionmentioning
confidence: 99%